ALAT ANGKUT SERBAGUNA UNTUK MENUNJANG KEGIATAN KELOMPOK TANI CEMPAKA II, DESA ANDAMAN 1, ANJIR PASAR, BARITO KUALA (Politeknik Perkeretaapian Indonesia Madiun, 2023)
The following program of Mandatory Serving Lecturers involves the Implementation Team of the Mechanical Engineering Study Program, Lambung Mangkurat University with partners from farmer groups. Mitra is a farmer group located in Andaman Village, Anjir Pasar District, Barito Kuala Regency. Some of the problems faced by Partners at this time are the less than optimal use of tractors, where tractors are only used as plow tools, and the plowing time is only about 4 months, when the plowing season is over, the tractors are only stored and not used for 8 months. These problems made the PKM team from the mechanical engineering study program at Lambung Mangkurat University invite to cooperate with farmer groups, where the PKM team provided knowledge and assistance in the form of goods, especially by designing a conveyance with a tractor drive. The methods used in this activity include literature studies, tool design, tool manufacture, handover of tools to partners. The results of the activity obtained a design and conveyance, where the conveyance is driven by a tractor and can be used by farmers to carry out harvesting activities and transport for other purposes. The manufacture of this conveyance can answer the partner's problems to maximize the work of the tractor which was previously only used for 4 months to be throughout the year